Implementasi LATURA Diffuser Aromaterapi Anti Stress Berbasis WiFi Dengan Kontrol Smartphone - Ranisa Oktaviyanti; Izzal Ihsani; Bagus Dwi Cahyono (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2024)
An individual's sleep quality can be hindered by the presence of very bright light, therefore, this research aims to create a device that can enhance the effectiveness and quality of sleep using LATURA (Universal Sleep Lamp), whose light intensity can be controlled using a WIFI and Bluetooth-enabled smartphone. Data collection in this study involves testing the device, accompanied by a survey of public responses after using this tool. The data analysis technique employs a tool performance test. The results of this research indicate that the success rate of LATURA shows that the system's effectiveness, as seen from public responses after using the device, has a success rate of 78%, where, on average, people are satisfied with the created device.